Observe the following: 1 = 1 2
2 + 3 + 4 = 3 2
3 + 4 + 5 + 6 + 7 = 5 2
4 + 5 + 6 + 7 + 8 + 9 + 1 0 = 7 2
… … 2 0 1 8 + 2 0 1 9 + 2 0 2 0 + . . . . . . . . . . . . . . . . . . . . . + 6 0 5 2 = n 2 what is n = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution.(+1)
I have just simply take the arithmetic average in the way from the taken numbers as shown: n 2 = ( 2 2 0 1 8 + 6 0 5 2 ) 2 = 4 0 3 5 2 , what is probably the less advanced way to solve it. The red number is our answer.
If you observe carefully the number of terms in every sequence is the square of the resulting number . 1 ( 1 t e r m ) = 1 2
2 + 3 + 4 ( 3 t e r m s ) = 3 2
3 + 4 + 5 + 6 + 7 ( 5 t e r m s ) = 5 2
4 + 5 + 6 + 7 + 8 + 9 + 1 0 ( 7 t e r m s ) = 7 2
… …
2 0 1 8 + 2 0 1 9 + 2 0 2 0 + . . . . . . . . . + 6 0 5 2 ( n t e r m s ) = n 2 Now, we have to find the value of n .
The numbers 2 0 1 8 , 2 0 1 9 , 2 0 2 0 , . . . . . , 6 0 5 2 are n terms in arithmetic progression with a = 2 0 1 8 , d = 1 . The last term in an A.p is given by the formula :
T n = a + ( n − 1 ) d
⟹ 6 0 5 2 = 2 0 1 8 + ( n − 1 ) 1 ⟹ n + 2 0 1 7 = 6 0 5 2
⟹ n = 4 0 3 5
Problem Loading...
Note Loading...
Set Loading...
( 6 0 5 2 + 6 0 5 1 + … + 2 0 2 0 + 2 0 1 9 + 2 0 1 8 ) − ( 2 0 1 7 + 2 0 1 6 + … + 5 + 4 + 3 + 2 + 1 ) = n 2
1 8 3 1 6 3 7 8 − 2 0 3 5 1 5 3 = 1 6 2 8 1 2 2 5
1 6 2 8 1 2 2 5 = n 2
∴ the answer is 4 0 3 5